Effectiveness of Deep Phet Interactive Simulation Improving Understanding of The Concept of Material Change - Gunawan, Ade; Heliawati, Leny; Permanasari, Anna (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2023)
The rapid development of technology demands optimal use in the education sector in order to achieve sustainable progress. Integrating technology in the learning process, especially through the application of interactive simulations, not only provides clear visual representations of scientific concepts, but also increases student involvement in learning, stimulates curiosity, and supports the formation of deeper understanding. One platform that stands out in this regard is Physics Education Technology (PhET), which provides realistic and easy-to-use simulations. Through PhET, students can conduct virtual experiments and immediately see the results. This research aims to evaluate the effectiveness of using PhET interactive simulations in increasing students' understanding of the concept of chemical material changes, by applying a learning model Discovery Learning. The research method applied is quantitative with a quasi-experimental design Nonequivalent Control Group Design, involving two groups of class 10 students at Madrasah Aliyah Bogor Regency. Analysis results Paired T-Test in the experimental group showed a score of 0.000 smaller than 0.05, indicating a significant difference between the pretest and posttest scores. This illustrates the positive impact of using PhET simulations on improving student understanding. The results of the N-Gain analysis show an average value of 0.5, indicating that PhET's effectiveness in improving students' understanding has moderate criteria. Further evaluation is needed to understand the factors that influence the effectiveness of PhET in this learning context.